Exploring the Relationship of Organizational Justice with Chinese Prison Staff Life Satisfaction - Lambert, Eric G. (The prison journal, 2022)
The bulk of the limited research on prison staff life satisfaction has been conducted in Western nations, particularly in the U.S., and only two studies have explored the relationship between organizational justice and life satisfaction, both of which only examined two of the four dimensions of justice. The current study investigated how all four dimensions of organizational justice (informational, interpersonal, distributive, and procedural) were related to life satisfaction among Chinese prison staff. The ordinary least squares (OLS) regression analysis indicated that informational, procedural, and distributive justice had significant positive effects on life satisfaction. Interpersonal justice had an insignificant effect.